Treatment of relapsed/refractory paediatric aggressive B‐cell non‐Hodgkin lymphoma. (6th March 2020) - Moleti, Maria L.; Testi, Anna M.; Foà, Robin
Summary: Aggressive B‐cell non‐Hodgkin lymphoma (B‐NHL) accounts for ≈60% of NHL in children/adolescents. In newly diagnosed Burkitt lymphoma and diffuse large B‐cell lymphoma, short intensive multiagent chemotherapy is associated with a five‐year event‐free survival of around 90%. Very few children/adolescents with aggressive B‐NHL show a relapsed/refractory (r/r) disease. The outcome is poor, with cure rates <30%, and there is no standard of care. Rituximab‐containing salvage regimens may provide a complete/partial response in 60–70% of cases. However, long‐term survival is <10% for non‐transplanted patients. Autologous or allogeneic haematopoietic stem cell transplant is, nowadays, the best option for responding patients, with survival rates around 50%. The benefit of autologous versus allogeneic HSCT is not clear. Numerous novel therapies for r/r B‐NHL are currently being tested in adults, including next‐generation monoclonal antibodies, novel cellular therapy strategies and therapies directed against new targets. Some are under investigation also in children/adolescents, with promising preliminary results.